Dialectic : the pulse of freedom - Bhaskar, Roy (Verso, 1993)
This book attacks purely analytical modes of thinking. Bhaskar develops a critical realist philosophy, which isolates the definition of being in terms of knowledge as the characteristic flaw of traditional philosophy. He conceives a "transformational" model of society and sees social science as explanatory, and therefore of assistance to political projects of emancipation. Concerned to bridge the gap between philosophy and politics, "Dialectic" argues that critical realism provides the basis of a completely new and general methodology for the human sciences. This book also contains an account of the history of Western philosophy, from its pre-Socratic origins to its contemporary post-modernist forms.